A new human mobility at the time of Covid-19 in the Rome Metropolitan Area - Armando Montanari (Belgeo)
Human mobility during the centuries of industrial development has long been studied using interpretative models in which movements inside and outside urban areas have been considered in relation to successive phases of economic development. In more recent times the study of mobility has highlighted the overlapping of phenomena hitherto considered to be unrelated, such as commuting, tourism and migration. The hybrid nature of sundry phenomena has required a distinction to be made: production-related mobility and consumption-related mobility. Measures introduced to combat the Covid-19 pandemic have brought further changes to reference parameters in this sphere. At this early stage we have some clues as to the possible development of human mobility in the future. We may realistically imagine that large urban areas will no longer be viewed as areas of concentration and overlap of all human activities. It is therefore necessary to look again at the parameters of human mobility in relation to new time and space parameters.